2021
DOI: 10.1016/j.celrep.2021.108788
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of glial progenitor cells during the neurogenesis-to-gliogenesis switch in the developing human cerebral cortex

Abstract: Highlights d EGFR + cells sharply increase at the start of human gliogenesis d EGFR + cells contain a high proportion of progenitor cells from different lineages d EGFR + SPARCL1 + OLIG2 + cells are more like astrocytes at the transcriptional level d EGFR + astrocyte progenitor cells are mainly distributed in the OSVZ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 65 publications
(93 reference statements)
10
65
0
Order By: Relevance
“…We re-analyzed published single-cell RNA-Seq datasets, including 3,355 EGFR ? cells from human frontal cortex at GW21-GW26 [35] and 33,976 cells from human cortex at GW17-GW18 [36], in the context of our immunohistochemistry results, and provide evidence that human cortical EGFR ? tRGs generate bMIPCs that coexpress EGFR, ASCL1, OLIG2 and OLIG1.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…We re-analyzed published single-cell RNA-Seq datasets, including 3,355 EGFR ? cells from human frontal cortex at GW21-GW26 [35] and 33,976 cells from human cortex at GW17-GW18 [36], in the context of our immunohistochemistry results, and provide evidence that human cortical EGFR ? tRGs generate bMIPCs that coexpress EGFR, ASCL1, OLIG2 and OLIG1.…”
Section: Introductionsupporting
confidence: 58%
“…1F-H); these genes are typical markers for OPCs. This might be the reason why previous studies termed bMIPC as ''Pre-OPCs'' or ''Pri-OPCs'' (IPC types preceding committed OPC) [35,[46][47][48][49]. Slingshot analysis [50], predicting a developmental trajectory and pseudo-timeline progression of IPCs, suggest that bMIPCs give rise to OPCs (ASCL1 ?…”
Section: Scrna-seq Analysis Reveals Human Cortical Trg Lineage At Gw21-gw26mentioning
confidence: 99%
“…We have reported that astrocyte progenitors assemble in the ventral half of the spinal cord at E15.5 ( Karus et al, 2011 ). Significant heterogeneity of astrocytes has been concluded from transcriptome studies and bioinformatic analysis ( John Lin et al, 2017 ; Fu et al, 2021 ). However, tools to enrich and separately study these asserted subpopulations in the spinal cord still remain to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Activated EGFR recruits adapter proteins which in turn activates complex downstream signaling cascades [35]. Emerging evidence indicates that EGFR signaling plays an important role in oligodendrogenesis [27,[36][37][38][39][40][41]. While EGFR knock-out appeared to reduce the density of OPCs and mature oligodendrocytes in corpus callosum [36], enhancing EGFR signaling by intraventricular infusion of EGF induced type B cells to differentiate into oligodendrocytes [38].…”
Section: Discussionmentioning
confidence: 99%